Current status and future challenges of CAR-T cell therapy for osteosarcoma - Li, Shizhe; Zhang, He; Shang, Guanning (Frontiers in Immunology, 2023)
Osteosarcoma, the most common bone malignancy in children and adolescents, poses considerable challenges in terms of prognosis, especially for patients with metastatic or recurrent disease. While surgical intervention and adjuvant chemotherapy have improved survival rates, limitations such as impractical tumor removal or chemotherapy resistance hinder the treatment outcomes. Chimeric antigen receptor (CAR)-T cell therapy, an innovative immunotherapy approach that involves targeting tumor antigens and releasing immune factors, has shown significant advancements in the treatment of hematological malignancies. However, its application in solid tumors, including osteosarcoma, is constrained by factors such as low antigen specificity, limited persistence, and the complex tumor microenvironment. Research on osteosarcoma is ongoing, and some targets have shown promising results in pre-clinical studies. This review summarizes the current status of research on CAR-T cell therapy for osteosarcoma by compiling recent literature. It also proposes future research directions to enhance the treatment of osteosarcoma.